Tracing the Historical Roots of Urban Transformation: The Case of Portoviejo, Ecuador - CHOEZ-GARCÉS , Kelvin; GUILLÉN-VIVAS , Mirian; LOOR , Ignacio (Journal of Ecohumanism, 2024)
This paper examines the historical trajectory of Portoviejo, Ecuador, to address how urban planning often overlooks the significance of historical processes, leading to fragmentation and neglect of culturally important spaces. While urban transformation literature has explored the socio-economic, environmental, and infrastructural drivers of change, a gap remains in understanding the specific historical contexts that shape cities in developing countries. This study aims to bridge this gap by exploring key moments in Portoviejo’s development, including its colonial foundation, natural disasters, and modernization efforts, and how they have shaped its urban form. Using a mixed-methods qualitative approach, the research analyses 63 historical documents and local archives, combined with Geographic Information System (GIS) mapping to trace urban growth and spatial reorganization. The findings reveal that Portoviejo’s development has been shaped by colonial policies, infrastructural changes such as the introduction of the railway, and natural disasters that led to urban fragmentation and informal settlements. The study highlights that understanding the historical trajectory of cities is essential for developing urban planning strategies that are resilient and contextually grounded. For practitioners, this research underscores the importance of integrating historical insights into planning processes to ensure development aligns with the socio-cultural identity and long-term resilience of cities.